2023
DOI: 10.11604/pamj.2023.45.142.39771
|View full text |Cite
|
Sign up to set email alerts
|

Health care seeking behaviours of pregnant women in rural Amhara, Ethiopia: a qualitative study of perceptions of pregnant women, community members, and health care providers

Abstract: Introduction in Ethiopia, increasing access to basic antenatal and neonatal health services may improve maternal and newborn survival. This study examined perceptions regarding antenatal health seeking behaviors from pregnant women, their families, community members, and health care providers in rural Amhara, Ethiopia. Methods the study was conducted in four rural districts of the Amhara region of Ethiopia. A total of forty participants who were living and working withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A study conducted in Ambo town, Oromia Regional State, revealed that the utilization of maternal health services was 39.7% for antenatal care, 28.7% for delivery services, and 19% for postnatal care [ 15 ]. Similarly, a study in the Amhara region revealed a low prevalence of maternal healthcare service utilization, with only 77% of women receiving Antenatal care (ANC) and 37% receiving postnatal care [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Ambo town, Oromia Regional State, revealed that the utilization of maternal health services was 39.7% for antenatal care, 28.7% for delivery services, and 19% for postnatal care [ 15 ]. Similarly, a study in the Amhara region revealed a low prevalence of maternal healthcare service utilization, with only 77% of women receiving Antenatal care (ANC) and 37% receiving postnatal care [ 16 ].…”
Section: Introductionmentioning
confidence: 99%